Abnormal gene expression of proinflammatory cytokines and their membrane-bound receptors in the lymphocytes of depressed patients - Rizavi, Hooriyah S.; Ren, Xinguo; Zhang, Hui; Bhaumik, Runa; Pandey, Ghanshyam N. (Psychiatry research, 2016)
Abnormalities of protein levels of proinflammatory cytokines and their soluble receptors have been reported in plasma of depressed patients. In this study, we examined the role of cytokines and their membrane-bound receptors in major depressive disorder (MDD). We determined the protein and mRNA expression of proinflammatory cytokines, interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and mRNA expression of their membrane-bound receptors in the lymphocytes from 31 hospitalized MDD patients and 30 non-hospitalized normal control (NC) subjects. The subjects were diagnosed according to DSM-IV criteria. Protein levels of cytokines were determined by ELISA, and mRNA levels in lymphocytes were determined by the qPCR method. We found that the mean mRNA levels of the proinflammatory cytokines IL-1β, IL-6, TNF-α, their receptors, TNFR1, TNFR2, IL-1R1 and the antagonist IL-1RA were significantly increased in the lymphocytes of MDD patients compared with NC. No significant differences in the lymphocyte mRNA levels of IL-1R2, IL-6R, and Gp130 were observed between MDD patients and NC. These studies suggest abnormal gene expression of these cytokines and their membrane-bound receptors in the lymphocytes of MDD patients, and that their mRNA expression levels in the lymphocytes could be a useful biomarker for depression.